2007
DOI: 10.1093/hmg/ddm351
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the role of DNA repair gene polymorphisms on risk of glioma

Abstract: Much of the variation in inherited risk of glioma is likely to be explained by combinations of common low risk variants. The established relationship between glioma risk and exposure to ionizing radiation led us to examine whether variants in the DNA repair genes contribute to disease susceptibility. We evaluated 1127 haplotype-tagging single-nucleotide polymorphisms (SNPs) supplemented with 388 putative functional SNPs to capture most of the common variation in 136 DNA repair genes, in five unique case-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 18 publications
1
48
2
Order By: Relevance
“…Expression of CAF-1 has been associated with cell proliferation in breast cancer (31), deregulation of DNA repair in squamous cell carcinoma (32), and genomic instability and cancer susceptibility in the recessively inherited Bloom syndrome (14). Furthermore, activating single nucleotide polymorphisms within the CHAF1A gene strongly correlate with glioma tumorigenesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CAF-1 has been associated with cell proliferation in breast cancer (31), deregulation of DNA repair in squamous cell carcinoma (32), and genomic instability and cancer susceptibility in the recessively inherited Bloom syndrome (14). Furthermore, activating single nucleotide polymorphisms within the CHAF1A gene strongly correlate with glioma tumorigenesis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Although none of these results are sufficient to propose "accurate" risk factors as in familial syndromes, they represent a new era in understanding brain tumor formation. Variants of DNA repair genes such as ERCC1, ERCC2, GLTSCR1, PRKDC, MGMT and CHAF1A have been shown to be significantly associated with glioma and/or glioma subtypes (Wei et al, 1997;Hegi et al, 2005;Wiencke et al, 2005;Yang et al, 2005;Bethke et al, 2007;Felini et al, 2007). ATM and cell cycle genes have been reported to be associated with meningioma and glioblastoma and BRIP-1 was associated with meningioma (Malmer et al, 2007;Rajaraman et al, 2007; Bethke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that another SNP (rs243356) of CHAF1A was associated with glioma risk (32). This suggests that CHAF1A may contribute to gliomagenesis and warrants further investigation.…”
Section: Random Forests Analysis Of Snps Cancer Epidemiol Biomarkers mentioning
confidence: 99%